Systems thinking, economics, and Islamic economics - Fontaine, Rodrigue Ancelot Harvey (WAIM, 2024)
This study is a literature review. It investigates how systems thinking has been applied in economics. This field has become known as “feedback economics”. An overview of feedback economics is presented first. The study then explores some of the papers in Islamic economics incorporating systems thinking that have been published. Most of these studies have focused on poverty alleviation. This combination of systems thinking, and Islamic economics seem to hold much potential for new areas of research in the field of Islamic economics.